Plasmid Profile, Curing Analysis, and antibacterial Activity of Alcea arebellensis plant Against Multidrug Resistance Staphylococcus aureus - Zirak F. A. Abdulrahman; Khadija Kh.M.Barzani; Aryan A. Rasheed (Tikrit Journal of Pure Science)
A total of  50 Staphylococcus aureus isolates were identified from burn , otitis media, wound and urine infection from patient admitted to the central lab and internal lab of teaching hospital and Rizgary hospital in Erbil city during the period 10thNovember 2011 to 30th March 2012. All the isolate identified according to Microscopical, cultural and biochemical tests. S. aureus tested for antibiotics susceptibility test using  agar diffusion method .The antibiotics susceptibility testing showed that  49(98%) , 48(96%), 48(94%), 9(18%),8(10%), 7(14%), and 4(8%), were resistant to chloramphenicol , Amikacin, ampicillin, Vancomycin ,Cefotaxime, Cefazolin ,and ceftriaxone but all the isolates were sensitive to amoxicillin. Also the results showed that isolate no.38 was resistant to seven antibiotics under study which contain five plasmids with molecular weight more than 10 kbp. The results also revealed that 5(10%), 25(50%), and 20(40%) of S.aureus were reported to produce alpha, beta, gamma hemolysis respectively. Results of plasmid curing experiments revealed that elevated temperature at 46oC were completely remove the plasmid that harbor antibiotic resistance gene for the antibiotic understudy while for bleomycin at 50µg/ml had lower effect. The antibacterial activity of aqueous and alcoholic extract of flowers and leaves of the Alcea arebelensis was studied against some resistant isolates of S. aureus, the results showed the inhibitory effect of plant extracts against selected isolates except the alcohol leaf extract which showed no inhibitory activity against all studied bacterial isolates.